Sudden and unexpected death in Sami areas in Norway - A qualitative study of the significance of religiosity in the bereavement process - Silviken, Anne; Gundersen, Lena Slettli; Berntsen, Gro; Dyregrov, Kari (Medical University of Vienna, 2015)
Sudden and unexpected death represents a severe life event incorporating multiple stressors and is potentially more traumatizing than natural deaths. Religiosity is an important resource in everyday life and may be especially important during times of loss. The aim of this paper is to explore the significance of religiosity in the coping process after sudden death, using a qualitative semi-structural in-depth interview guide to investigate the experiences of 30 bereaved people from different Sámi areas in Northern Norway. The findings showed that religiosity might be a great source of help in the grieving and coping process.